2020
DOI: 10.1111/cas.14603
|View full text |Cite
|
Sign up to set email alerts
|

DRP1 promotes lactate utilization in KRAS‐mutant non‐small‐cell lung cancer cells

Abstract: Metabolic alterations are well documented in various cancers. Non-small-cell lung cancers (NSCLCs) preferentially use lactate as the primary carbon source, but the underlying mechanisms are not well understood. We developed a lactate-dependent cell proliferation assay and found that dynamin-related protein (DRP1), which is highly expressed in KRAS-mutant NSCLC, is required for tumor cells to proliferate and uses lactate as fuel, demonstrating the critical role of DRP1 in the metabolic reprogramming of NSCLC. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Studies have revealed that CRS activates glial cells to release proinflammatory factors, such as interleukin-1β (IL-1β) and tumor necrosis factor α (TNF- α) ( Deak et al, 2015 ), which in turn promotes apoptosis, ultimately leading to apoptosis. BAX is a proapoptotic protein belonging to the Bcl-2 family, and it acts in conjunction with Drp1 to increase mitochondrial membrane permeability and division, which facilitates the release of cytochrome c (Cyt C) from the mitochondria into the cytoplasm ( Reed, 1997 ; Sugioka et al, 2004 ; Hu et al, 2020 ). CREB serves an important role in neuronal regeneration, synaptic growth, learning, and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that CRS activates glial cells to release proinflammatory factors, such as interleukin-1β (IL-1β) and tumor necrosis factor α (TNF- α) ( Deak et al, 2015 ), which in turn promotes apoptosis, ultimately leading to apoptosis. BAX is a proapoptotic protein belonging to the Bcl-2 family, and it acts in conjunction with Drp1 to increase mitochondrial membrane permeability and division, which facilitates the release of cytochrome c (Cyt C) from the mitochondria into the cytoplasm ( Reed, 1997 ; Sugioka et al, 2004 ; Hu et al, 2020 ). CREB serves an important role in neuronal regeneration, synaptic growth, learning, and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, PINK1 -/- cells contained 29.2% fragmented mitochondria compared with 77.7% in the vector group ( Figure 6 ). It has been reported previously that upon Drp1 deletion, the mitochondrial morphology in HCT116 cells was more intermediate ( 48 50 ). In our study, we inhibited Drp1 expression in HCT116 cells by small interfering RNA (siRNA), and the knockdown efficacy was determined by western blot ( Figure S4C ) .…”
Section: Resultsmentioning
confidence: 70%
“…Consistent results were obtained in the KRas mutant non-small-cell lung cancer (NSCLC), where DRP1 orchestrated a metabolic rewiring to promote lactate utilization and ROS production suppression [ 62 ]. In the same type of tumor, DRP1 was involved in metabolic rearrangements that favored resistance to chemotherapy [ 63 ].…”
Section: Fusion and Fission Event In The Onset And Progression Of mentioning
confidence: 66%